Dieu à l’épreuve de la pente. Spatialités du catholicisme en Maurienne - Sophie-Anne Olivier; Lionel Laslaz (M@ppemonde)
This article aims to present the spatial manifestations of Catholicism throughout the territory of the Maurienne valley, with the presumption that the mobility, at all scales, is a major feature in a reconstructed aggregated parish. Studying the ecclesial structure of Savoie in general and Maurienne in particular allows us to inventory the basic structures through which Catholic space is manifested, with its plurality of actors. It also allows us to map reticular logics and polarities at various moments. Though the practice of Catholicism is universal, its expression remains profoundly contextual. This implies taking into account the specificities of the valley’s social context where tourism dominates. It is equally necessary to consider phenomena such as appropriation, valuation, and representation tied to specific spatial contexts, a necessary step in their (de)construction. Finally, the article lays the foundation for a geographical study of religious practice in Maurienne